Knowledge about epilepsy by students and staff of a school in Fortaleza-CE - Silvânia Maria Mendes Vasconcelos; Lucilane Maria Sales da Silva; Thereza Maria Magalhães Moreira; Rita Neuma Dantas Cavalcante de Abreu; Eliane Magalhães de Brito; Janaiana Lemos Uchoa; Maria Rocineide Ferreira da Silva (Universidade de Fortaleza, 2009)
Objective: To assess the knowledge of teachers, students and employees of a school about epilepsy. Methods: A descriptive cross-sectional, quantitative study held in a school in Fortaleza - CE. The universe consisted of all students and staff at the school who met the following inclusion criteria: to be a student or employee of the night shift, to be 18 years old or above. Data collection occurred in September 2007, by applying a structured questionnaire. From 69 questionnaires, 50 were completed by students, 11 by teachers and eight by other school employees. We divided the sample into two groups: staff (employees and teachers) and students. Results: The results show that 22% of staff believed that one of the forms of epilepsy transmission occurred through saliva. It was found that 98% of staff and 94% of students said that epilepsy is a neurological disorder. Concerning the control of the disease, 94% of students and 78% of staff believed that it occurs by taking the medication daily. Among the respondents, 29% of staff and 22% of students felt that people with epilepsy have difficulty in school learning. It was also observed that most participants scored appropriate procedures to be adopted in the seizure. Conclusion: The research determined gaps in the knowledge about epilepsy in the studied sample.